LEGAL ANALYSIS AGAINST SEX GRATIFICATION ON COURT DECISION NUMBER: 87 /PID.SUS /TPK /2013 / PN.BDG - Destyani, Ade; Gilalo, J. Jopie (DERECHTSSTAAT, 2018)
Gratification in criminal law in Indonesia is a gift in the broad sense of discounts, commissions, interest-free loans, travel tickets, and other facilities as a mode to influence a policy that is contrary to its duties and obligations as a public servant or state administrator. Giving is no exception, including the provision of services in the form of sex. However, in Law Number 20 Year 2001 concerning the Eradication of Corruption, the enforcement of categorized gratification law on difficult law enforcement, as its proof is bound by laws and regulations concerning the law of evidence, therefore this type of corruption is not can use the conventional legal system. The alternative to overcome the limitations of Law Number 31 Year 1999 in conjunction with Law No. 20 of 200 on Corruption Eradication of Gratification of sex law is to fill the legal vacuum by using the authority of judges during the examination of cases in court. Court verdict Number: 87/ PID.SUS /TPK /2013 Â PN.BDG found the fact that one of the witnesses in the court provided information that the defendant requested sexual services every Thursday or Friday night, but in legal considerations the fact was not considered, it can be used as evidence against the defendant. The authors, judges in giving consideration of the decision need to elaborate, examine and examine more deeply the facts about the sex gratification associated with the explanation of Article 12 B paragraph 1. For the long term also need to absorb Islamic law as solving the problem of sexual gratification so that found the right solution in legal reform in Indonesia.